Small RNAs in plant defense responses during viral and bacterial interactions: similarities and differences - Peláez, Pablo; Sanchez, Federico (Frontiers in Plant Science, 2013)
Small non-coding RNAs (sncRNAs) constitute an important class of gene expression regulators that control different biological processes in most eukaryotes. In plants, several small RNA silencing pathways have evolved to produce a wide range of small RNAs (sRNAs) with specialized functions. Evidence for the diverse mode of action of the small RNA pathways has been highlighted during plant-microbe interactions. Host sRNAs and small RNA silencing pathways have been recognized as essential components of plant immunity. One way plants respond and defend against pathogen infections is through the small RNA silencing immune system. To deal with plant defense responses, pathogens have evolved sophisticated mechanisms to avoid and counterattack this defense strategy. The relevance of the small RNA-mediated plant defense responses during viral infections has been well established. Recent evidence points out its importance also during plant-bacteria interactions. Herein, this review discusses recent findings, similarities and differences about the small RNA-mediated arms race between plants and these two groups of microbes, including the small RNA silencing pathway components that contribute to plant immune responses, the pathogen-responsive endogenous sRNAs and the pathogen-delivered effector proteins.